Audience reception of acculturation in parenting style on Indonesian-Korean YouTube channel - Briandana, Rizki; Dwityas, Nindyta Aisyah; Mayde, Putri Calista (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
The aim of this study is to investigate the audience reception of acculturation in parenting style on the Indonesian-Korean YouTube channel